Déclaration commune en réponse à un rapport publié par Mario Beaulieu, député / Joint Statement in Response to Report Released by Mario Beaulieu, M.P. - English Language Arts Network (ELAN); Quebec Writers' Federation (QWF); Quebec Drama Federation (QDF); Association of English-language Publishers of Quebec (AELAQ) (2023)
Keywords: Official Language Minority Community (OLMC)

COVID-19 Update - Quebec Drama Federation (QDF) (2022)

A New Confinement That Will Leave Its Mark - Morse, Rachel; Régnier, Laurence (2022)

QDF's Membership & Community Summit Schedule - Quebec Drama Federation (QDF) (2022)

Brief on Bill 96 : An Act Respecting French, the Official and Common Language of Quebec - Neal, Christopher; Barlow, Julie; Rodgers, Guy; Maturo, Nick (English-Language Arts Network (ELAN), 2021)

Brief on Bill 96 : An Act Respecting French, the Official and Common LAnguage of Quebec Submitted by the Quebec Writers' Foundation (QWF), The English Language Arts Network (ELAN), and the Quebec Drama Federation (QDF) - Quebec Writers' Federation (QWF); English Language Arts Network (ELAN); Quebec Drama Federation (QDF) (2021)
As part of Quebec’s English-speaking community, as artists, storytellers, dramatists and performers embedded in and contributing to Quebec’s cultural life, we are deeply troubled by the character, spirit and content of Bill 96, and the negative impact it threatens to have on Quebec’s English-language arts community.

Fringe Frenzy Bingo - Quebec Drama Federation (QDF)